National Vital Object Security Management Approach in Supporting Sustainable Tourism in Geothermal Power Plants - Imam Supriyadi (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to analyze and prioritize security management approaches—preemptive, preventive, and repressive—to safeguard the Dieng Geothermal Power Plants, designated as a National Vital Object (Obvitnas), while simultaneously promoting sustainable tourism development in the Dieng area. Balancing national security requirements with community-based tourism initiatives presents a complex challenge that this study seeks to address. Methodology: A qualitative research method was employed, integrating the Analytical Hierarchy Process (AHP) to systematically prioritize security strategies. Data collection involved structured surveys and in-depth interviews with three key stakeholder groups: company management, security personnel, and community leaders. Triangulation was used to validate findings and ensure a comprehensive understanding of diverse stakeholder perspectives. Main Findings: The results reveal that the preemptive security approach is prioritized as the most critical strategy, emphasizing the importance of community involvement, partnership programs, and environmental initiatives to ensure the safety of the geothermal plant while fostering trust and collaboration with local communities. Repressive and preventive approaches, while still important, are ranked lower in effectiveness for achieving both security and tourism sustainability objectives. The study highlights that fostering proactive community engagement and ecological stewardship can serve as dual drivers of security and socio-economic development. Novelty/Originality of this Study: This research offers a novel integration of security management and sustainable tourism principles, proposing a community-centered security framework specifically adapted for Obvitnas like Dieng GPPs. It provides new insights into how national energy infrastructure can be protected without hindering, and even supporting, local tourism growth and community empowerment.